2016
DOI: 10.1002/adom.201600601
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Photon Excitation Temperature Nanosensors Based on a Conjugated Fluorescent Polymer Doped with a Europium Probe

Abstract: A strongly fluorescent organic semiconducting polymer doped with a highly temperature dependent fluorescent europium(III) complex is converted into a nanosized material that is capable of optically sensing temperature (T) in the range from 0 to 50 °C via two‐photon excitation at 720 nm. The nanosensors are prepared from a blue‐fluorescent polyfluorene that acts as both a light‐harvesting antenna (to capture two‐photon energy) and an energy donor in a fluorescence resonance energy transfer (FRET) system. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Temperature-dependent luminescence properties of materials based on rare earth elements have been widely studied for their applications in non-contact optical thermometry. [1][2][3][4] Many of these investigations have focused on the uorescence intensity ratio (FIR) of two thermally coupled excited energy levels (TCEELs) of rare earth ions such as Pr 3+ , 5 Nd 3+ , 6,7 Gd 3+ , 8 Dy 3+ , 9,10 Ho 3+ , 11,12 Er 3+ , [13][14][15][16][17][18] and Tm 3+ , 19 and have frequently involved upconversion (UC) luminescence. 6,8,[11][12][13][14][15][16]19 In particular, the FIR technique based on TCEELs has the advantage of requiring few measurements since it is not susceptible to uctuations of excitation power.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature-dependent luminescence properties of materials based on rare earth elements have been widely studied for their applications in non-contact optical thermometry. [1][2][3][4] Many of these investigations have focused on the uorescence intensity ratio (FIR) of two thermally coupled excited energy levels (TCEELs) of rare earth ions such as Pr 3+ , 5 Nd 3+ , 6,7 Gd 3+ , 8 Dy 3+ , 9,10 Ho 3+ , 11,12 Er 3+ , [13][14][15][16][17][18] and Tm 3+ , 19 and have frequently involved upconversion (UC) luminescence. 6,8,[11][12][13][14][15][16]19 In particular, the FIR technique based on TCEELs has the advantage of requiring few measurements since it is not susceptible to uctuations of excitation power.…”
Section: Introductionmentioning
confidence: 99%
“…35). 147 In the obtained nanocomposite 46, efficient fluorescence resonant energy transfer (FRET) from the light-harvesting polyfluorene antenna to the doped Eu(III) complex occurred. Under the two-photon excitation at 720 nm at rt, dual emissions in the blue and red region were observed.…”
Section: Multi-component Coordination Copolymers and Assembliesmentioning
confidence: 99%
“…Over the last decades, the majority of the phosphors were based on the rare‐earth ions‐activated luminescent materials. Researchers have revealed that the rare‐earth ions‐activated luminescent materials showed extensive applications in various fields, such as, optical thermometry, white‐LED, bioimaging, fingerprint identification, etc Notably, the rare‐earth compounds exhibit similar chemical and physical behaviors; as a consequence, costly refinement, separation, and purification technologies are necessary which make them very expensive. Therefore, designing a highly efficient non‐rare‐earth ions‐activated phosphors is crucial.…”
Section: Introductionmentioning
confidence: 99%